Six Letters on Andreas Kalvos from Mario Vitti to Antonis Indianos - Ioannou, Kyriakos (Études helléniques / Hellenic Studies, 2007)
The six letters written by Mario Vitti to Antonis Indianos (1960-1962), and found in the latter’s archives, bear witness to their common interest in Andreas Kalvos, who was not well known yet at the time. The letters cover the period during which Kalvos was settling in England.